2019
DOI: 10.1111/apa.14808
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to oxygen saturation targets increased in preterm infants when a higher target range and tighter alarm limits were introduced

Abstract: Aim European consensus guidelines published in May 2013 recommended a target peripheral capillary oxygen saturation (SpO2) range of 90–95% for preterm infants. These were incorporated into guidelines at the Karolinska University Hospital, Sweden, in November 2013. This study compared clinical practice before and after those local guidelines. Methods We included infants who were born between 23 + 0 and 30 + 6 weeks from January 1, 2013 to December, 31 2015 and received intensive care in two Karolinska units. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The risk of hypoxaemia decreased, but the risk of hyperoxaemia increased. 20,21 Interestingly, this change only marginally altered the risk of the PaO 2 exceeding 10.7 kPa.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The risk of hypoxaemia decreased, but the risk of hyperoxaemia increased. 20,21 Interestingly, this change only marginally altered the risk of the PaO 2 exceeding 10.7 kPa.…”
Section: Discussionmentioning
confidence: 96%
“…The appropriate definition of a safe PaO 2 target range remains uncertain. Several authors have used a range of 5.3-10.7 kPa (40-80 mm Hg), [18][19][20][21][22] but others proposed an upper limit of 12 kPa (90 mm Hg). 23,24 Using the former definition, PaO 2 values were less likely outside the target range (18.5%) compared to SpO 2 and SaO 2 readings raising the question of whether the defined target range is too wide.…”
Section: Discussionmentioning
confidence: 99%
“…European consensus guidelines published in May 2013 recommended a target peripheral capillary oxygen saturation range of 90–95% for preterm infants. Klevebro et al compared clinical practice before and after these were incorporated into local guidelines at Karolinska University Hospital, Sweden, in November 2013 . Higher saturation target and tighter alarm limits led to higher mean oxygen saturation and greater adherence to the targets, but increased the time with hyperoxaemia.…”
Section: Oxygen Dilemma Balances Growth and Development With Retinopamentioning
confidence: 95%
“…In this issue of Acta Paediatrica , Klevebro et al report the results from a retrospective study carried out in Stockholm before and after the 2013 European consensus guidelines were integrated into local practice at the Karolinska Institutet. The study comprised 399 infants born between 23 and 30 weeks of gestation who received supplemental oxygen during the first three weeks of life.…”
mentioning
confidence: 99%
“…Klevebro et al found that the higher SpO2 target range resulted in less time with hypoxaemia. The late effects of intermittent hypoxaemia were addressed in a post hoc analysis by the Canadian Oxygen Trial and were associated with an increased risk of late death or disability at 18 months of age, suggesting that further preventative research is needed .…”
mentioning
confidence: 99%